2018
DOI: 10.1002/bit.26569
|View full text |Cite
|
Sign up to set email alerts
|

Engineered CRISPR/Cas9 system for multiplex genome engineering of polyploid industrial yeast strains

Abstract: The CRISPR/Cas9 system has been widely used for multiplex genome engineering of Saccharomyces cerevisiae. However, its application in manipulating industrial yeast strains is less successful, probably due to the genome complexity and low copy numbers of gRNA expression plasmids. Here we developed an efficient CRISPR/Cas9 system for industrial yeast strain engineering by using our previously engineered plasmids with increased copy numbers. Four genes in both a diploid strain (Ethanol Red, 8 alleles in total) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…Our previous work has shown that it is difficult to express heterologous genes in C. tropicalis , so codon optimization of the entire gene would be the best way forward (L. Zhang et al, ). Using either the monocistronic or polycistronic transcript version, the efficiency of double gene deletion in C. tropicalis was lower than that in S. cerevisiae (Y. P. Zhang et al, ) and industrial yeast (Lian et al, ), but higher than that in Yarrowia lipolytica (Holkenbrink et al, ). Part of the reason for this lack of efficiency may be that the “HH‐N20 target sequence‐sgRNA scaffold‐HDV” construction is not the most suitable for multiple RNA processing in C. tropicalis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has shown that it is difficult to express heterologous genes in C. tropicalis , so codon optimization of the entire gene would be the best way forward (L. Zhang et al, ). Using either the monocistronic or polycistronic transcript version, the efficiency of double gene deletion in C. tropicalis was lower than that in S. cerevisiae (Y. P. Zhang et al, ) and industrial yeast (Lian et al, ), but higher than that in Yarrowia lipolytica (Holkenbrink et al, ). Part of the reason for this lack of efficiency may be that the “HH‐N20 target sequence‐sgRNA scaffold‐HDV” construction is not the most suitable for multiple RNA processing in C. tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous report showed that the abundance of intracellular sgRNA correlated with Cas9 editing efficiency in yeast (Lian et al, 2018;Ryan et al, 2014;Schwartz, Hussain, Blenner, & Wheeldon, 2016). When ADE2 was targeted, six different CRISPR-Cas9 cassettes with different promoters to deliver sgRNA were constructed in parallel (integrated at POX4 locus, Figure 4a) and transformed individually into C. tropicalis CU-206.…”
Section: Transient Crispr-cas9 Systemmentioning
confidence: 99%
“…A previously described protocol (Stovicek, Borodina, & Forster, ) was adopted for gene deletion and site‐specific integration of heterologous gene expression cassettes in HDL using Cas9 and gRNA expression plasmids with increased copy numbers (Lian, Bao, et al, ). For SAH1 disruption in HDL, the gRNA plasmid pKan100‐sg.SAH1 was constructed by Gibson Assembly using primers HDL‐SAH1‐gRNA‐F and HDL‐SAH1‐gRNA‐R with the plasmid pKan100‐ADE2.1 (Lian, Bao, et al, ) as the template. The homology‐directed repair donor was generated by overlap extension PCR using primer sets HDL‐SAH1CZ1‐F and HDL‐SAH1CZ1‐R as well as HDL‐SAH1CZ2‐F and HDL‐SAH1CZ2‐R with the HDL genomic DNA as the template.…”
Section: Methodsmentioning
confidence: 99%
“…Cas9‐mediated gene editing can create any type of mutation, but many applications require accurate base editing at the single‐nucleotide level with no off‐target impact. Progress has been made to increase the accuracy and efficiency of CRISPR‐Cas9 editing in laboratory strains (Ferreira, Skrekas, Nielsen, & David, ; Lian, Bao, Hu, & Zhao, ), but the process of precise gene editing still has potential for improvement. A recent study looked at the relatively low gene editing efficiency and the loss of heterozygosity (LOH) that occurs when CRISPR‐Cas9 is used in complex genomes, such as aneuploid genomes or genomes with increased heterozygosity, which are often found in industrial yeast strains (Gorter de Vries et al, ).…”
Section: Crispr For Rapid Multiplex Engineering Of Cell Factoriesmentioning
confidence: 99%